ANALISIS PELAKSANAAN PROGRAM KESEHATAN LINGKUNGAN PERIODE JANUARI-DESEMBER 2013 DI PUSKESMAS KABUPATEN TAPANULI TENGAH TAHUN 2014 - erianto Silaban (Lingkungan dan Kesehatan Kerja, 2015)
Environmental health effort was one of the principal public health centre, which includes housing, health a privy, clean water, disposal of waste, waste water and sanitation a public place and food processing.This study was aimed to know analysis program execution in environmental health public health central at tapanuli disrict.This research was descriptive design and informer in this research is power health programs officers in central tapanuli health department with an six informants.The results of research that we have known majoring in sanitation but, facilities and infrastructures already exist but not yet complete, a guideline and technical had been available in all public health centre, program of environmental health had walked in all the existing health in the county of tapanuli district .For the house of healthy fully 85 percent of the houses qualified, a privy that qualifies as many as 75 % of people, the scope of the house qualified health, as much as 85 percent of the houses, the quality of the drinking water that qualify as many as 100 % of a house, the number of public places that qualifies as many as 75 %.After the achievement of targets program 2010 ( KEPMENKES No..Hk.03.01 / 160 / i / 2010), all the coverage program environmental health in public health centre central Tapanuli district has reached target. Suggested to dept. of regency central tapanuli to may increase the number of officers sanitation after the number of population in the area ex-coworker, need to be fund management size maximum that the program environmental health way it target that had been established.